2012
DOI: 10.1007/s10562-012-0822-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface Species of Supported Ruthenium Catalysts in Selective Hydrogenation of Levulinic Esters for Bio-Refinery Application

Abstract: Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to c-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru 0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Ru based catalysts have shown high performance to reduce levulinic acid or its esters to GVL (Hengne et al, 2012). XPS studies revealed that a higher extent of Ru 0 species in case of carbon supported Ru could account for its higher hydrogenation activity as compared to Ru on other supports.…”
Section: Hydrogenation Of Levulinic Acid To C-valerolactone (Gvl)mentioning
confidence: 99%
“…Ru based catalysts have shown high performance to reduce levulinic acid or its esters to GVL (Hengne et al, 2012). XPS studies revealed that a higher extent of Ru 0 species in case of carbon supported Ru could account for its higher hydrogenation activity as compared to Ru on other supports.…”
Section: Hydrogenation Of Levulinic Acid To C-valerolactone (Gvl)mentioning
confidence: 99%
“…These initial results are highly promising since significantly more harsh reaction conditions (200°C, 30-40 bar H 2 ) are generally reported in the literature for these reactions to achieve similar yields of γ-valerolactone with catalysts containing transition metals like Pt, Ru and Rh. 29,30,35,36 More detailed exploration of the γ-valerolactone formation from methyl levulinate and derivatives will be the subject of future work.…”
Section: Selective Hydrogenation Of Arenes With Rhnps/pvpmentioning
confidence: 99%
“…Among them, Ru catalysts shown high performance to reduce levulinic acid or its esters 59 to GVL. Thus, Manzer 60 showed that GVL can be obtained with 97 % yield by hydrogenation of levulinic acid in dioxane as a solvent at 423 K with 5 wt% Ru/C, while 99 % yield could be obtained in a continuous process in supercritical CO 2 over a Ru/SiO 2 catalyst.…”
mentioning
confidence: 99%